Robotics for Cochlear Implantation Surgery: Challenges and Opportunities. Issue 7 (August 2021) - Panara, Kush; Shahal, David; Mittal, Rahul; Eshraghi, Adrien A.
Abstract : Objectives: Recent advancements in robotics have set forth a growing body of evidence for the clinical application of the robotic cochlear implantation (RCI), with many potential benefits. This review aims to summarize these efforts, provide the latest developments in this exciting field, and explore the challenges associated with the clinical implementation of RCI. Data Sources: MEDLINE, PubMed, and EMBASE databases. Study Selection: A search was conducted using the keywords "robotics otolaryngology, " "robotic cochlear implant, " "minimally-invasive cochlear implantation, " "minimally-invasive mastoidectomy, " and "percutaneous cochlear implant" with all of their synonyms. Literature selection criteria included articles published in English, and articles from 1970 to present. Results: The use of robotics in neurotology is a relatively new endeavor that continues to evolve. Robotics is being explored by various groups to facilitate in the various steps of cochlear implant surgery, including drilling a keyhole approach to the middle ear for implants, inner ear access, and electrode insertion into the cochlea. Initial clinical trials have successfully implanted selected subjects using robotics. Conclusions: The use of robotics in cochlear implants remains in its very early stages. It is hoped that robotics will improve clinical outcomes. Although successful implants with robots are reported in the literature, there are some challenges that need to be addressed before this approach can become an acceptable option for the conventional cochlear implant surgery, such as safety, time, efficiency, and cost. However, it is hoped that further advancements in robotic technology will help in overcoming these barriers leading to successful implementation for clinical utility. Abstract : Supplemental Digital Content is available in the text